PENGARUH KOMUNIKASI DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN J&T EXPRESS MUARADUA KABUPATEN OGAN KOMERING ULU SELATAN - Dwi Sapitri; Mardiah Kenamon; Tati Herlina; Riki Adriant (Fakultas Ekonomi dan Bisnis Universitas Baturaja, 2023)
The purpose of this research was to determine the Influence of Communicationand Work Discipline on the Performance of Employees at J&T ExpressMuaradua, Ogan Komering Ulu Selatan. The data collection technique used inthis research was through distributing questionnaires. Data processing was doneusing SPSS version 25.0. The population in this research consisted of 32employees of J&T Express Muaradua, Ogan Komering Ulu Selatan Regency. Theanalysis method used was a quantitative method using Multiple Linear Regressionanalysis. The results of the analysis explained that the t-value for each dependentvariable Communication (x1) was 4.683, while Work Discipline (x2) was 0.545,which was greater compared to the t-table value of 2.04523. This indicated thatCommunication (x1) had a significant influence on employees’ performance,while the Work Discipline (x2) variable did not have a significant influence on theperformance of J&T Express employees in Muaradua, Ogan Komering UluSelatan Regency. The calculated F-value of 11.021 was greater than the tabulatedF-value of 3.33, indicating that both Communication and Work Disciplinesimultaneously had a significant influence on the performance of J&T Expressemployees in Muaradua, Ogan Komering Ulu Selatan Regency. The coefficient ofdetermination (Adjusted R2) value of 0.432 meant that the contribution ofCommunication and Work Discipline to Employees’ Performance was 43.2%,while the remaining 56.8% was influenced by other variables not included in thisresearch, such as Skills, work motivation, work culture (Afandi; 2018:87)